Analisis Kebutuhan Pendidikan Pencegahan Perilaku Berisiko pada Remaja di Kabupaten Magelang - Silmi, Fina Idamatus (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2020)
Background: Adolescents are vulnerable to risky behaviors such as smoking, alcohol consumption, and risky sexual behavior. The involvement of one risky behavior can lead to other risky behaviors. Therefore, it is necessary to prevent risky behavior to ensure adolescents' health. This study aimed to prevent risky behaviors according to adolescents' needs.Method: This was an observational research with the cross-sectional method. Data were obtained using a questionnaire through interviews with respondents. The research subjects were adolescents aged 15-24 years. Samples were randomly selected, as much as 100 adolescents. Results: There were 2 categories of adolescents, they were